The Effectiveness of Meta-cognitive Skills Training on the Motivational Structure and Academic Performance of Drop-out Students - Mokhtari, Mohammad; Hassanzadeh, Ramazan; Mirzaeeyan, Bahram (International Clinical Neuroscience Journal, 2019)
Background: Meta-cognitive skills training through giving meaning to information and making a logical connection between new and previously learned content, enables students to learn better and improve their academic performance. The present study was carried out to investigate the effectiveness of meta-cognitive skills training on the motivational structure and academic performance of drop-out students. Methods: This study considered as semi-experimental research which has used the pretest-post-test with control group design. In this study, the statistical population included all drop-out male and female students of the Sari Agricultural Sciences and Natural Resources University (They entered the university in 2014 and considered as drop-out students for at least two years). Thirty students were selected using the purposive sampling method, who randomly divided into two groups of experimental (n=15) and control (n=15). Meta-cognitive skills taught to the experimental group within four sessions. The Motivational Structure Questionnaire (MSQ) and academic performance report card were used to collect data. Covariance analysis and SPSS-24 software used for data analysis. Results: According to the results of covariance analysis, there is a significant difference between the experimental and control groups (P < 0.001). Therefore, it can conclude that meta-cognitive skills training a significant effect on the motivational structure and students’ academic performance. Conclusion: Due to the results of this study, it is imperative that university officials pay attention to the effect of the meta-cognitive training program on the motivational structure and performance of drop-out students and provide the proper context for relevant skills training in the counseling department, the department of social affairs and educational field.